Genetic Diversity and Positive Selection Analysis of Classical Swine Fever Virus Envelope Protein Gene E2 in East China under C-Strain Vaccination - Hu, Dongfang; Lv, Lin; Gu, Jinyuan; Chen, Tongyu; Xiao, Yihong; Liu, Sidang (Frontiers in Microbiology, 2016)
Classical swine fever virus (CSFV) causes an economically important and highly contagious disease of pigs worldwide. C-strain vaccination is one of the most effective ways to contain this disease. Since 2014, sporadic CSF outbreaks have been occurring in some C-strain vaccinated provinces of China. To decipher the disease etiology, 25 CSFV E2 genes from 169 clinical samples were cloned and sequenced. Phylogenetic analyses revealed that all 25 isolates belonged to subgenotype 2.1. Twenty-three of the 25 isolates were clustered in a newly defined subgenotype, 2.1d, and shared some consistent molecular characteristics. To determine whether the complete E2 gene was under positive selection pressure, we used a site-by-site analysis to identify specific codons that underwent evolutionary selection, and seven positively selected codons were found. Three positively selected sites (amino acids 17, 34, and 72) were identified in antigenicity-relevant domains B/C of the amino-terminal half of the E2 protein. In addition, another positively selected site (amino acid 200) exhibited a polarity change from hydrophilic to hydrophobic, which may change the antigenicity and virulence of CSFV. The results indicate that the circulating CSFV strains in Shandong province were mostly clustered in subgenotype 2.1d. Moreover, the identification of these positively selected sites could help to reveal molecular determinants of virulence or pathogenesis, and to clarify the driving force of CSFV evolution in East China.